Seroprevalence and Risk Factors of Inkoo Virus in Northern Sweden - Evander, Magnus; Putkuri, Niina; Eliasson, Mats; Lwande, Olivia Wesula; Vapalahti, Olli; Ahlm, Clas (The American Journal of Tropical Medicine and Hygiene, 2017)
The mosquito-borne Inkoo virus (INKV) is a member of the California serogroup in the family Bunyaviridae, genus Orthobunyavirus. These viruses are associated with fever and encephalitis, although INKV infections are not usually reported and the incidence is largely unknown. The aim of the study was to determine the prevalence of anti-INKV antibodies and associated risk factors in humans living in northern Sweden. Seroprevalence was investigated using the World Health Organization Monitoring of Trends and Determinants in Cardiovascular Disease study, where a randomly selected population aged between 25 and 74 years (N = 1,607) was invited to participate. The presence of anti-INKV IgG antibodies was determined by immunofluorescence assay. Seropositivity for anti-INKV was significantly higher in men (46.9%) than in women (34.8%; P <0.001). In women, but not in men, the prevalence increased somewhat with age (P = 0.06). The peak in seropositivity was 45-54 years for men and 55-64 years for women. Living in rural areas was associated with a higher seroprevalence. In conclusion, the prevalence of anti-INKV antibodies was high in northern Sweden and was associated with male sex, older age, and rural living. The age distribution indicates exposure to INKV at a relatively early age. These findings will be important for future epidemiological and clinical investigations of this relatively unknown mosquito-borne virus. Peer reviewed